MENINGKATKAN MOTORIK HALUS ANAK KELOMPOK B MELALUI TEKNIK FINGER PAINTING DI PENDIDIKAN ANAK USIA DINI ISLAM TERPADU - Naila Afrilia; Indra Bangsawan; Achmad Fadlan (STKIP Subang, 2026)
Fine motor skills in early childhood are a developmental aspect requiring optimal stimulation due to their impact on learning readiness. Preliminary observations at the Mutiara Hati Integrated Islamic Early Childhood Education (PAUD) center in Jambi City revealed that the fine motor skills of children in Group B were low, with an achievement level of only 35%; consequently, a more engaging and effective instructional strategy was needed. This study aimed to enhance children's fine motor skills through the implementation of finger painting techniques. The study employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted over two cycles—each comprising planning, implementation, observation, and reflection stages. The subjects were 15 children from Group B at the Mutiara Hati Integrated Islamic PAUD center. Data collection involved observation, documentation, and the assessment of child development. The results demonstrated that the finger painting technique successfully improved the children's fine motor skills incrementally. The achievement percentage for fine motor skills rose from 35% in the pre-cycle stage to 49.51% in Cycle I, reaching 82.37% in Cycle II. This improvement indicates that finger painting activities are effective in fostering eye-hand coordination, finger muscle strength, precision, and creativity. Thus, finger painting serves as an innovative instructional alternative for optimizing fine motor development in early childhood